Penerapan Strategi Pembelajaran Card Sort Kolaborasi Small Group Discussion Sebagai Upaya Meningkatkan Motivasi dan Prestasi Belajar Pendidikan Kewarganegaraan - Aisah Aisah; Nunuk Suryani; Siti Sutarmi Fadhilah (Universitas Sebelas Maret, 2018)
Citizenship is a lesson got from the elementary school to college level of education. It emphasizes on nation character building in order to be a well citizen which is putting his/ her right and obligation along with the constitution and law. Citizenship education is applied at all levels of education by means of developing knowledge obtained previously in order to be active at the instructional process for further level of education. In order to reach the goal as mentioned above, it is needed a teacher who knows in how to teach well by appltying convenient method towards its level and students’ capability. Facilities also play very important role to support the on going curriculum. It is necessary for the teacher to make a lesson plan before teaching the class. By doing so, the instructional process will run well and he. She will be able to develop their creativity as well with the students. They must have passion and motivation to to learn as the teachers will feel proud to give better for them. The topic of protection and human rights watch is one of the topics of citizenship lesson learnt in Junior High School Grade VII on the second semester in SMP Negeri 3 Surakarta.